1961
DOI: 10.2134/agronj1961.00021962005300020015x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Grasses and Legumes to Liming and Phosphorus Fertilization1

Abstract: Synopsis Species showed a differential response to lime and phosphorus rates on an acid subsoil material. There was a tendency for lime and phosphate to compensate for each other to some degree. The yield increase due to lime was apparent up to the point at which the exchangeable aluminum was immobilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Yield responses reflecting negative lime-P interactions on acidic soils high in soluble Al have been noted in pots with grasses and legumes as test plants (Shoop et al .• 1961) and under field conditions with several crop species (Sanchez & Salinas, 1981). Munns (1965) reported both positive and negative lime-P interactions in the growth of lucerne on a severely P-deficient soil under glasshouse conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Yield responses reflecting negative lime-P interactions on acidic soils high in soluble Al have been noted in pots with grasses and legumes as test plants (Shoop et al .• 1961) and under field conditions with several crop species (Sanchez & Salinas, 1981). Munns (1965) reported both positive and negative lime-P interactions in the growth of lucerne on a severely P-deficient soil under glasshouse conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Plant responses to lime and P on such soils have, particularly under glasshouse conditions, received much attention (Shoop, Brooks, Blaser & Thomas, 1961), with interactions between these amendments being frequently noted. However, despite the emphasis in recent years on the importance of nutrient interactions on farm profitability (Cooke, 1982;Wagner, 1981;1983), relatively few attempts have been made to verify the existence of such interactions under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in shoot Ca and Mg concentrations have been found after the addition of calcitic and dolomitic limes (9,32,33,34,35). These changes appeared to be largely dependent on the elemental composition of the material, the application 324 TYE, FULLEN, AND HOCKING rate and the particle size distribution and were the same factors considered responsible for the differences in soil pH.…”
Section: Tye Fullen and Hockingmentioning
confidence: 95%
“…Detrimental effects of low pH, including reduced shoot and root growth, lower vigor, and reduced competitive ability, occurred on strongly acid soils with pH below 5.5 (Murray and Foy, 1978). Maximum plant growth was obtained from about pH 6.0 to 7.0, with declining growth at higher pH (Shoop et al, 1961; Palazzo and Duell, 1974). Shoop et al (1961) also reported some reciprocal compensation of lime and P. The association of the lime response with amelioration of Al toxicity (Shoop et al, 1961; Fleming et al, 1974; Murray and Foy, 1978) and P response only to low rates of fertilizer on limed soils (Shoop et al, 1961) have essentially limited the recommendation and use of these soil amendments to somewhat modest levels for tall fescue.…”
mentioning
confidence: 96%
“…Previous evaluations of tall fescue on highly acid soils have shown responses to lime and P (Shoop et al, 1961; Palazzo and Duell, 1974; Murray and Foy, 1978). Both lime and P responses were evident within 14 d of plant emergence (Shoop et al, 1961), suggesting substantial benefits for seedling development. Differential responses to soil pH between cultivars and among individual plants within a cultivar have been obtained (Murray and Foy, 1978).…”
mentioning
confidence: 99%